THE STATUS OF VAGINAL MICROBIOCENOSIS IN CHRONIC SALPINGOOPHORITE AND ITS ASSESSMENT - Ziyayeva E`tiborhon Rasuljonovna; Abdullaeva Malika Azimovna (Bright Mind Publishing, 2025)
The long course of chronic salpingo-oophoritis, the use of various antibiotics for treatment lead to complex changes in the microbiocenosis of the body of sick women. These changes lead to a more severe course of SSO. A deep study of this condition allows you to restore the microbiocenosis of the vagina and cervix and improve the results of treatment.
Keywords: Chronic salpingoophoritis, bichenozis, mikrobichenoz.